The relation between parent ratings and direct assessments of preschoolers' numeracy skills. (February 2021) - Lin, Joyce; Napoli, Amy R.; Schmitt, Sara A.; Purpura, David J.
Abstract: This study examines whether parent ratings of children's numeracy skills are more related to direct assessments of corresponding skills, broad numeracy, or other cognitive skills, to inform how to best utilize parent ratings in research. Children in the sample ( N = 129) ranged from 3.07 to 5.95 years old and 52.3% were male. Most (81%) of the children were White. Parents rated their children's counting, arithmetic, and numeral identification skills. Children were directly assessed on these skills, broad numeracy, and other cognitive skills (i.e., expressive vocabulary, executive function). Parent ratings of children's numeracy abilities varied in terms of whether they were more related to directly assessed corresponding skills or broad numeracy abilities. Aggregated parent ratings predicted broad numeracy abilities more than other cognitive skills, providing evidence for discriminant validity. Findings inform how parent ratings may be used when children cannot be directly assessed, such as when large-scale parent surveys are used. Highlights: The specificity of parent ratings of children's numeracy skills are examined. Findings indicated parent ratings were domain- but not skill-specific. Aggregated parent ratings predicted directly assessed general numeracy. Findings inform how children's numeracy abilities may be measured.